Terahertz magnetoplasmon resonances in coupled cavities formed in a gated two-dimensional electron gas - Park,S; Zonetti,S; Parker-Jervis,R; Wu,J; Wood,C; Li,LH; Davies,G; Linfield,E; Sydoruk,O; Cunningham,J (Optics Express, 2021)
We report on both experiments and theory of low-terahertz frequency range (up to 400 GHz) magnetoplasmons in a gated two-dimensional electron gas at low (<4K) temperatures. The evolution of magnetoplasmon resonances was observed as a function of magnetic field at frequencies up to ∼400 GHz. Full-wave 3D simulations of the system predicted the spatial distribution of plasmon modes in the 2D channel, along with their frequency response, allowing us to distinguish those resonances caused by bulk and edge magnetoplasmons in the experiments. Our methodology is anticipated to be applicable to the low temperature (<4K) on-chip terahertz measurements of a wide range of other low-dimensional mesoscopic systems.